Selenium Dioxide Promoted α-Keto N-Acylation of Sulfoximines Under Mild Reaction Conditions - Baranwal S.; Gupta S.; Kandasamy J. (My University, 2025)
A practical method for the synthesis of α-ketoamides of sulfoximines was developed from NH-sulfoximines and acetophenones using selenium dioxide as an oxidant. The reactions proceeded under mild conditions in the absence of any additives and provided good to excellent yields of α-keto-N-acylsulfoximines. Moreover, the optimized condition was well-suited to the task of α-ketoacylation of sulfoximines with phenylacetaldehyde and arylacetylenes. α-Hydroxy N-acylsulfoximines were obtained in good yields from α-keto N-acylsulfoximines via reduction or Grignard reactions. © 2021 Wiley-VCH GmbH.